BUILDING EXPERT MAPS FOR ERGONOMETRIC, COMPOSITIONAL AND COLORS SCHEME EVALUATION OF MACHINE CONTROL PANELS - Bankova, Aleksandrina; Tsoneva, Zoya (Innovation in Woodworking Industry and Engineering design, 2022)
In the present study, an in-depth literature analysis was made regarding the theoretical problems of signs and sign-information systems as means of visual communication, about the essence of graphic design and its possibilities for creating a sign-information system as a means of communication in the "man-machine" system. , of the means of presentation of information and control (SPI) and the control bodies (OU) and the ergonomic requirements (standards) on panels of machines during their design. Based on this analysis, a system of design and evalua-tion criteria was developed regarding:- the arrangement (arrangement) of the elements of the sign-information system;- graphic design – composition and color, graphic shapes and signs;Тhe following methods were employed during the research: theoretical analysis of the problems related to the sign-information systems for visual communication as well as the ergo-nomic requirements and the graphic design requirements for composition, colors, use of graphic forms and signs; analysis of the variants of sign-information systems, applied on panels (control and indicating equipment), conducted through a system of criteria in order to establish the ad-vantages and the disadvantages of their design; graphical presentation of the analysis results employing frequency tables and graphical images – bar diagrams and others.